Application of the Knuth-Morris-Pratt Algorithm on Android-based Money Recognition Applications for the Blind - Yoga Prasetia; Ghulam Asrofi Buntoro; Dwiyono Ariyadi (Institute of Computer Science (IOCS), 2021)
Blind is a term used to define the human condition given a privilege by God in the sense of sight, this condition makes blind people have a little difficulty in carrying out daily activities. Money is a primary human need and is very important for daily buying and selling transactions. Indonesian money, especially paper money, has an embossed line that can help people with visual impairments a little, but there is some money circulating in the market that is damaged or missing lines of appearance which makes it difficult for blind people to recognize the nominal of the money. The research was conducted at the “AISYIYAH” Orphanage for the Blind in Ponorogo by conducting several interviews with blind people, the informants provided information that they could recognize money on a daily basis but only applies to banknotes with good condition and the latest output, for damaged banknotes. or the old output is hard to identify. To help the blind recognize money, an android-based application was designed with the Knuth-Morris-Pratt algorithm which is a type of string matching algorithm. This algorithm is a development algorithm from the previous algorithm, namely the Brute Force algorithm. The final result of this study shows that the android application designed using the Knuth-Morris-Pratt algorithm is able to recognize nominal money with an accuracy rate of 100%.